Pengelolaan Program SMP Negeri 56 Satu Atap Di Daerah Terpencil Bengkulu Utara - Mona Liza; Connie (Manajer Pendididikan, 2023)
This study aims to describe program management at One Roof 56 Public Middle School in a remote area of North Bengkulu. This research is a qualitative descriptive research. Research data obtained from interviews, observation and documentation. Research data analysis includes data reduction, data presentation, verification and drawing conclusions. The results of the researchers showed that program management at One-roof 56 Public Middle School in a remote area of North Bengkulu had been carried out well. The North Bengkulu One Roof 56 Public Middle School needs to realize solutions in dealing with obstacles in order to improve the quality of education in schools and realize expectations and increase the attractiveness of the community